Fossil plant relative abundances indicate sudden loss of Late Triassic biodiversity in East Greenland. - McElwain, J; Wagner, P; Hesselbo, S (2009)
The pace of Late Triassic (LT) biodiversity loss is uncertain, yet it could help to decipher causal mechanisms of mass extinction. We investigated relative abundance distributions (RADs) of six LT plant assemblages from the Kap Stewart Group, East Greenland, to determine the pace of collapse of LT primary productivity. RADs displayed not simply decreases in the number of taxa, but decreases in the number of common taxa. Likelihood tests rejected a hypothesis of continuously declining diversity. Instead, the RAD shift occurred over the upper two-to-four fossil plant assemblages and most likely over the last three (final 13 meters), coinciding with increased atmospheric carbon dioxide concentration and global warming. Thus, although the LT event did not induce mass extinction of plant families, it accompanied major and abrupt change in their ecology and diversity.